1997
DOI: 10.1017/s0952523800012153
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of biogenic amines in fundal layers in chickens with normal visual experience, deprivation, and after reserpine application

Abstract: Previous experiments in chickens have shown that dopamine released from the retina may be one of the messengers controlling the growth of the underlying sclera. It is also possible, however, that the apparent relationship between dopamine and myopia is secondary and artifactual. We have done experiments to assess this hypothesis. Using High Pressure Liquid Chromatography with electrochemical detection (HPLC-ED), we have asked whether changes in dopamine metabolism are restricted to the local retinal regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 26 publications
8
76
0
Order By: Relevance
“…[74][75][76][77][78][79] Interestingly, both GABA and dopamine have been implicated in the regulation of eye growth. [80][81][82][83][84][85][86][87][88] In the rat retina, the epinephrine-synthesizing enzyme phenylethanolamine N-methyltransferase (PNMT) has been localized to amacrine cell populations 89 and retinal epinephrine levels have been reported to rise upon light exposure 90,91 ; but there is no further evidence for a role of epinephrine or norepinephrine in retinal visual processing of any vertebrate species examined. In spite of this, a-adrenoceptors are present on retinal neurons.…”
Section: Ocular A-adrenoceptors and Possible Mechanism Of Actionmentioning
confidence: 99%
“…[74][75][76][77][78][79] Interestingly, both GABA and dopamine have been implicated in the regulation of eye growth. [80][81][82][83][84][85][86][87][88] In the rat retina, the epinephrine-synthesizing enzyme phenylethanolamine N-methyltransferase (PNMT) has been localized to amacrine cell populations 89 and retinal epinephrine levels have been reported to rise upon light exposure 90,91 ; but there is no further evidence for a role of epinephrine or norepinephrine in retinal visual processing of any vertebrate species examined. In spite of this, a-adrenoceptors are present on retinal neurons.…”
Section: Ocular A-adrenoceptors and Possible Mechanism Of Actionmentioning
confidence: 99%
“…8 Furthermore, the decrease of retinal DOPAC was restricted only to the deprived area of the retina during partial deprivation. 9,10 In chickens, DOPAC recovered to normal levels after removal of the formdeprivation goggle. 11 Unlike FDM in chickens, recent studies showed that retinal dopamine levels remained unaltered in FDM C57BL/6 mice.…”
mentioning
confidence: 97%
“…More interestingly, studies using chicks also found that there was only reduction of DOPAC in the section of the deprived area in the retina and also only the deprived area grew further (Ohngemach et al, 1997;Stone et al, 2006). The results of the studies might be indicating that there is a negative association between retinal dopamine release and ocular growth, also the refraction can be affected via alteration of dopamine level results from deprived vision.…”
Section: The Action Of Dopamine and The Eyementioning
confidence: 88%
“…DOPAC was found to reduce in negative lens wearing chicks (Ohngemach et al, 1997). More interestingly, studies using chicks also found that there was only reduction of DOPAC in the section of the deprived area in the retina and also only the deprived area grew further (Ohngemach et al, 1997;Stone et al, 2006).…”
Section: The Action Of Dopamine and The Eyementioning
confidence: 92%
See 1 more Smart Citation